The Case for Using Free Gingival Grafts in the Anterior Mandible: Clinical Case Reports - Fouda, Mohamed; Aluckal, Eby; Abraham, Abe (Journal of Orofacial Research, 2022)
Although free gingival grafts (FGG) are considered to be one of the most predictable procedures for increasing keratinized tissue around teeth, it still has drawbacks mainly because of the color mismatch between the grafted site and the surrounding gingiva, and the increased morbidity due to the necessity of having two surgical sites, a donor site where we harvest the graft and a recipient site. Several attempts were made to replace free gingival grafts with techniques that offer better esthetics such as subepithelial connective tissue graft placed through a tunnel or a coronally advanced flap, or techniques that also offer less morbidity to the patient such as the use of guided tissue membranes or acellular dermal matrix as a replacement for palatal tissue. And although root coverage can be achieved predictably through many of these techniques, free gingival grafts still have their place in modern dentistry. These two cases demonstrate how free gingival graft would be the best choice to treat cases with a lack of keratinized tissue in the anterior mandible, especially in the presence of shallow vestibule and high frenal attachment.